ROS signalling – specificity is required - Møller, Ian M.; Sweetlove, Lee J. (Trends in plant science, 2010)
Reactive oxygen species (ROS) production increases in plants under stress. ROS can damage cellular components, but they can also act in signal transduction to help the cell counteract the oxidative damage in the stressed compartment. H 2O 2 might induce a general stress response, but it does not have the required specificity to selectively regulate nuclear genes required for dealing with localized stress, e.g. in chloroplasts or mitochondria. Here we argue that peptides deriving from proteolytic breakdown of oxidatively damaged proteins have the requisite specificity to act as secondary ROS messengers and regulate source-specific genes and in this way contribute to retrograde ROS signalling during oxidative stress. Likewise, unmodified peptides deriving from the breakdown of redundant proteins could help coordinate organellar and nuclear gene expression.